2012
DOI: 10.1002/app.34880
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the surface roughness of conducting polypyrrole thin‐film electrodes on the electrocatalytic reduction of nitrobenzene

Abstract: Conducting polypyrrole (PPy) thin‐film electrodes were prepared by the electropolymerization of pyrrole on gold‐coated glass plates. Films of various roughnesses were obtained by the variation of the scan rates during electropolymerization. These thin films were modified by doping with 6mM of the dopant NiCl2. The surface morphology of the films was studied by scanning electron microscopy and atomic force microscopy (AFM), which suggested films prepared with a high scan rate were rougher in nature than the fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…root‐mean‐square roughness ( R q ), average roughness ( R a ) and ten‐points mean roughness ( R z ), and a maximum deviation of Zn 1‐ x Fe x –LDH and Zn 1‐ x Fe x –oxyselenide were estimated from AFM data and are given in Table S1 (Supporting Information). From the obtained AFM data, it is observed that the nanosheets after selenization were rougher than the Zn 1‐ x Fe x –LDH nanosheet . Since the electrophysical–chemical properties of the material are strongly dependent on surface roughness, the as‐synthesized materials are expected to show distinct catalytic activities …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…root‐mean‐square roughness ( R q ), average roughness ( R a ) and ten‐points mean roughness ( R z ), and a maximum deviation of Zn 1‐ x Fe x –LDH and Zn 1‐ x Fe x –oxyselenide were estimated from AFM data and are given in Table S1 (Supporting Information). From the obtained AFM data, it is observed that the nanosheets after selenization were rougher than the Zn 1‐ x Fe x –LDH nanosheet . Since the electrophysical–chemical properties of the material are strongly dependent on surface roughness, the as‐synthesized materials are expected to show distinct catalytic activities …”
Section: Resultsmentioning
confidence: 99%
“…From the obtained AFM data, it is observed that the nanosheets after selenization were rougher than the Zn 1-x Fe x -LDH nanosheet. [47,48] Since the electrophysical-chemical properties of the material are strongly dependent on surface roughness, the as-synthesized materials are expected to show distinct catalytic activities. [49] Further, in order to get better insights into the structuralrelated information, high-resolution transmission electron microscope (HR-TEM) was carried out.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…Thus, detection and disposal of toxic and hazardous waste nitrobenzene have received a great deal of attention. For the reduction and treatment of nitrobenzene to aniline, many catalysts have been developed, including Ru nanoparticles, PdO/CuO nanoparticles, AuPt bipyramid nanoframes, AgAu Alloy nanodots, Cu–Zr amorphous alloys, Cu nanoparticles, and organic polymers. , However, most of these catalysts are metal-based or even precious-metal-based materials, and the high prices limit their wide application. As a result, it is crucial to develop cheap and easily available catalysts for the reduction of nitrobenzene.…”
Section: Introductionmentioning
confidence: 99%
“…However, the poor adhesion of PPy to the substrate or electrode is usually the main problem. Several methodologies have been studied to increase electrode–PPy adhesion, such as electrode functionalization [ 12 , 13 , 14 ], optimization of the polymerization parameters [ 9 , 15 ], and adhesion promoters [ 16 , 17 , 18 ]. Alkoxysilanes are a group of compounds that have been used for a long time as adhesion promoters between inorganic surfaces and polymeric matrixes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%